Upregulated Expression of TUBA1C Predicts Poor Prognosis and Promotes Oncogenesis in Pancreatic Ductal Adenocarcinoma via Regulating the Cell Cycle - Albahde, Mugahed Abdullah Hasan; Zhang, Piao; Zhang, Qiuqiang; Li, Guoqi; Wang, Weilin (Frontiers in Oncology, 2020)
Abstract Background Pancreatic ductal adenocarcinoma (PDAC) is a highly malignant disease and has the worst prognosis and survival rate. TUBA1C is a microtubule component implicated with multiple cancers. However, the clinical significance and biological functions of TUBA1C in the progression of PDAC remain unexplored. Methods The Cancer Genome Atlas (TCGA) and Gene Expression Profiling Interactive Analysis (GEPIA) data were employed to detect the TUBA1C mRNA expression and the relation between TUBA1C expression and overall survival (OS) in PDAC. Then, bioinformatic analysis was employed to determine the potential pathway and genes related to TUBA1C. Human pancreatic cancer tissue and adjacent nontumor tissues samples were detected by immunochemistry (IHC) staining, and the correlation between TUBA1C expression and the clinicopathological features were investigated. Meanwhile, TUBA1C expression in PDAC cell lines were evaluated by western blotting. Furthermore, functional assays including cell viability, apoptosis, cell cycle, wound healing assay, transwell assay and a xenograft tumor model were performed to determine the oncogenic role of TUBA1C in PDAC, respectively. Results TUBA1C was overexpressed in the PDAC tissues and cells. IHC analysis showed that the TUBA1C overexpression was associated with short OS. Bioinformatics analysis indicated that TUBA1C overexpression was mainly associated with cell cycle regulation. The downregulation of TUBA1C significantly suppressed cell proliferation, induced cell apoptosis and cycle arrest, and inhibited migration and invasion in PDAC cells. Furthermore, TUBA1C downregulation also inhibited tumor growth in vivo